Government Service Innovation for People with Disabilities: Lessons Learned from Ball Pick-Up Service - Razak, Andi Rosdianti; Dinar, Intan Fatima Tuzahrah; Elfiansya, Hafiz; Haerana, Haerana (Universitas Pancasakti, 2022)
The study utilized four innovation indicators of the public service program of the Gowa Regency Population and Civil Registration Service to determine the supporting factors in providing pick-up and drop-off services. Qualitative research with descriptive narrative techniques was used to explain the research findings by analyzing materials or research to determine their meaning, and then drawing conclusions. Community members and office workers were used as key informants, selecting three service employees and two additional informants based on a purposive sample approach. Two of the informants were people with disabilities who provide E-KTP services. Data collection techniques included interviews, observation, and documentation, while strategies for data analysis involved data reduction, data display, and drawing conclusions. The results of the research show that the football pick-up service meets the established innovation criteria, consisting of five innovation criteria: novelty, effectiveness, usefulness, transferability/replicability, and sustainability. The innovation of the pick-up service carried out by the Gowa Regency Population and Civil Registration Service is beneficial for companies that consistently innovate and for the community, with supporting elements including infrastructure, community involvement, and human resources/ball pick-up service staff.